Development of the omnidirectional transporting table based on omnidirectional driving gear. (18th March 2020) - Abe, Kazuki; Matsui, Gaku; Tadakuma, Kenjiro; Yamano, Mitsuhiro; Tadakuma, Riichiro
ABSTRACT: We present a new transporting device, the omnidirectional transporting table that exhibits a driving mechanism with two perpendicular degrees of freedom based on gear meshing. By implementing omnidirectional driving gear, it can simultaneously drive multiple carried objects (driven units) with different trajectories despite the fixed installation of the actuators to the ground frame. Since the top plate acts as the supporting mechanism for the driven units and the driven unit can pass from one driving spur gear to another, the driven unit range of motion is unlimited. This device also features intrinsic safety for human workers. In particular, because its driven mechanism is based on gear meshing, the driven unit can be positioned without a global positioning sensor. We established the control algorithm by modeling the mechanism of the device and produced a prototype. Results of path tracking and positioning accuracy experiments confirm that the control model and control algorithm are reasonable and that many specifications from the mechanism are realized. With its unique characteristics, the omnidirectional transporting table is very useful as a flexible production line in applications like multi-product, low-volume manufacturing because of its high affinity with cell production systems and industrial robots. GRAPHICAL ABSTRACT: